Understanding the crisis in harm reduction funding in Central and Eastern Europe - Michal Miovský; Silvia Miklíková; Viktor Mravčík; Jean-Paul Grund; Tereza Černíková (BMC, 2020)
Abstract Background The harm reduction (HR) approach to injecting drug use was rapidly adopted in Central Europe following the fall of the Iron Curtain. The associated social and economic transformation had significant consequences for drug policies in the region. A large number of emerging services have been dependent on funding from a wide range of national and/or local funding programmes, which continue to be unstable, and closely associated with political decisions and insufficient institution building. A sharp distinction is made between health and social services, often without regard to client input. The main objective of the paper is to identify the causes of the funding problems currently faced by HR services in the context of their history of institution building which represents a major threat to the future of HR services in the region. Methods Qualitative content analysis of documents was conducted in the development of two case studies of the Czech and Slovak Republics. The body of documentation under study comprised policy documents, including National Drug Strategies, Action Plans, ministerial documents, and official budgets and financial schedules, as well as documents from the grey literature and expert opinions. Results The insufficient investments in finalising the process of the institution building of HR services have resulted in a direct threat to their sustainability. An unbalanced inclination to the institutionalisation of HR within the domain of social services has led to a misperception of their integrity, as well as to their funding and long-term sustainability being endangered. In addition, this tendency has had a negative impact on the process of the institutionalisation of HR within the system of healthcare. Conclusion The case study revealed a lack of systemic grounding of HR services as interdisciplinary health-social services. The aftermath of the financial crisis in 2008 fully revealed the limitations of the funding system established ad hoc in the 1990s, which remains present until today, together with all its weak points. The entire situation is responsible for the dangerous erosion of the interpretation of the concept of harm reduction, which is supported by various stereotypes and false, or ideological, interpretations of the concept.